AI In Diplomacy: An Analysis Of The Role Of Artificial Intelligence In Multilateral Negotiations - Judijanto, Loso; Samaduri, Lutpi; Nampira, Ardi Azhar (Synergisia, 2025)
This research analyzes the role of artificial intelligence (AI) in multilateral diplomacy, with a focus on improving the efficiency and effectiveness of international negotiations. Applying a qualitative approach through literature research methods, this analysis collects and synthesizes relevant literature, including books, scientific journals, and policy reports that discuss the interaction between AI and diplomacy. AI has the potential to improve real-time data analysis, sentiment tracking, as well as predict the outcome of diplomatic scenarios, enabling diplomats to be more responsive to complex global challenges. However, the use of AI is also faced with ethical and security challenges, such as algorithmic bias, transparency issues, and the potential for a reduction in the role of humans in diplomatic decision-making. Therefore, it is important to develop a regulatory framework that ensures fair and transparent use of AI in the context of diplomacy. The study provides recommendations to stakeholders on the importance of human oversight and strong governance to optimize the benefits of AI in multilateral diplomacy, while also considering its ethical implications